Determinants of Loan Loss Provisions in Chinese Commercial Banks - Song, Yanyan (2019)
Bank loan loss provisions are important in maintaining banks’ overall stability and soundness. After the 2008 global economic crisis, higher provisioning requirements are adopted by banks, with the aim to accumulate loan loss reserves in good time in respond to rising level of risks in bad times. The aim of the study is to examine the determinants of loan loss provisioning behaviour by Chinese commercial banks in the post-crisis period. Income smoothing, capital management, procyclical and efficiency hypothesis are tested. Based on an unbalance panel of 163 Chinese commercial banks during 2012-2018, the results support the income smoothing hypothesis and procyclical hypothesis but not for capital management hypothesis. The increase of banks’ efficiency levels would raise the loan loss provisioning levels. The empirical results also indicate that publicly traded banks are more prudent in making more provisions and smooth income to a lesser extent than unlisted banks.